IMPROVING VO2MAX OF STUDENTS OF THE SPORTS COACHING EDUCATION STUDY PROGRAM GUNUNG LEUSER UNIVERSITY , ACEH THROUGH THE INTERVAL TRAINING METHOD - Afrizal; Evi Falona Br Nainggolan (Jurnal Penelitian Progresif, 2024)
The aim of this research is to determine the increase in VO2Max using the Interval Training training method in students of the Sports Coaching Education Study Program at Gunung Leuser University, Aceh. This research is experimental research. The research sample consisted of 78 people, with total sampling. The design used in the research is Pre Test–Post Test Group Design. The research instrument uses a bleep test. Hypothesis testing used the paired t-test analysis technique (independent sample t-test) using SPSS with a significance level of p=0.05. Descriptive data analysis. The results of data analysis using the paired t-test showed an increase after carrying out the Interval Training training method for 6 weeks with a frequency of 3 times a week with the results of the pre-test. The results of the paired t-test between pre-test and post-test data on students of the Sports Coaching Education Study Program at Gunung Leuser University, Aceh were obtained with a significance value of 0.000 (p < 0.05), which means there was a significant increase in VO2Max among students of the University's Sports Coaching Education Study Program. Mount Leuser Aceh.